Comparison Analysis of Developmentalism in Globalization Era: Indonesia Joko Widodo’s Presidency (2014-2019) and South Korea Moon Jae-In Presidency (2017-2020) - Mulyaman, Darynaufal; Ismail, Achmad; Carollina, Nadya; Zefanya, Morry (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
In the globalized age, freedom in capital and workforce movement, self expression, and information openness become vital, including in Asian countries like Indonesia and South Korea. Thus innovation and creativity have become an important key in recent eras. New kinds of innovation and creativity that are established by Asian countries sometimes are nostalgic policies by the previous regime of the government. Therefore, Indonesia still comes up with a kind of centralistic governance and planning with a twist of free and liberal market policy, a developmental style of New Order governance to some extent. Hence, why is developmentalism in Indonesia still relevant? Even when there are shifts in the regimes and globalization process of the world. This paper argues that the policy series that has been initiated in Indonesia under President Joko Widodo is still part of developmentalism because of the historical and political context in a broader sense on developmentalism, therefore still relevant in Indonesia. This paper also uses the South Korean case of current policy under President Moon Jae-In to compare and assign Indonesian developmentalism relevancy as South Korea can be seen as one of the successful examples of developmentalism yet liberal country.